The Effects of External Uncertainties against Monetary Policy Uncertainty on IRANIAN Stock Return Volatility Using GARCH-MIDAS Approach - Razmi, Seyedeh Fatemeh; Bajgiran, Bahareh Ramezanian; Razmi, Seyed Mohammad Javad; Oroumieh, Kiana Baensaf (International Journal of Energy Economics and Policy, 2020)
This study investigates the effect of two external uncertainties of US Economic Policy Uncertainty (EPU) and OPEC oil price uncertainty against domestic monetary policy uncertainty on Iran’s stock return volatility. Reaching this goal, GARCH-MIDAS approach is employed that makes it possible using different variables with different frequencies during the period from January 2009 to September 2017. The research uses Iran’s stock return with high frequency and other variables with low frequencies. The results of the GARCH-MIDAS model show that the increase in the US EPU, the OPEC’s oil price uncertainty and Iran’s monetary policy uncertainty increase volatility of Iranian stock returns. US EPU significantly impact on Iran’s stock return volatility, which implies that the Iranian stock market has gradually merged into the global economy. However, oil price uncertainty has stronger effect on the stock return volatility than US EPU. In addition, monetary policy uncertainty is the strongest in affecting stock return uncertainty. Iranian policymakers can reduce the volatility of stock return by decreasing domestic monetary policy uncertainty. Keywords: US Economic Policy Uncertainty, Monetary policy, Oil Price, Iran’s stock volatility, GARCH-MIDAS JEL Classification: G12 DOI: https://doi.org/10.32479/ijeep.9176